2015
DOI: 10.3109/10253890.2015.1004538
|View full text |Cite
|
Sign up to set email alerts
|

Acute stress and working memory in older people

Abstract: Several studies have shown that acute stress affects working memory (WM) in young adults, but the effect in older people is understudied. As observed in other types of memory, older people may be less sensitive to acute effects of stress on WM. We performed two independent studies with healthy older men and women (from 55 to 77 years old) to investigate the effects of acute stress (Trier Social Stress Test; TSST) and cortisol on WM. In study 1 (n = 63), after the TSST women (but not men) improved their perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
26
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 59 publications
7
26
1
1
Order By: Relevance
“…In contrast, only young men had picture recall impaired by the TSST ( Hidalgo et al., 2015 ). In healthy older participants, the TSST improved working memory performance in women but not men, and for digit span forward but not digit span backward, suggesting a specific effect on memory span but not the executive component of working memory ( Pulopulos et al., 2015 ). Of course, stress has a multifaceted impact on cognition.…”
Section: Impact Of Agementioning
confidence: 95%
“…In contrast, only young men had picture recall impaired by the TSST ( Hidalgo et al., 2015 ). In healthy older participants, the TSST improved working memory performance in women but not men, and for digit span forward but not digit span backward, suggesting a specific effect on memory span but not the executive component of working memory ( Pulopulos et al., 2015 ). Of course, stress has a multifaceted impact on cognition.…”
Section: Impact Of Agementioning
confidence: 95%
“…Glucocorticoid receptors are widely distributed in the hippocampus and in the prefrontal cortex, which are involved in declarative memory and attention and executive function, respectively (Lupien et al, 1999). Whereas some studies found that lower cortisol levels were related to worse attentional performance (Pulopulos et al, 2015;Vedhara et al, 2000), other studies reported an association between higher cortisol levels and worse attention and processing speed (Beluche et al, 2010;Fonda, Bertrand, O'Donnell, Longcope, &McKinlay, 2005;Franz et al, 2011;Lee et al, 2007;MacLullich et al, 2005). In addition, Lupien et al (1999) observed an inverted-U pattern between cortisol and working memory performance that has an attentional component (Mirsky, Anthony, Duncan, Ahearn, & Kellam, 1991) and is also mediated by prefrontal cortex functioning.…”
Section: Allelesmentioning
confidence: 99%
“…In addition, it is characterized by a psychomotor excitement with a heightened response to fear and behavior blindness. These symptoms disappear following the removal of the stimulus (5)(6)(7)(8). By contrast, chronic stress is a response of body to long-duration, uncontrollable emotional pressure, and presentation of high blood pressure, muscle tissue damage, growth inhibition, immune system suppression and metal health damage (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%